2009
DOI: 10.1143/jjap.48.091404
|View full text |Cite
|
Sign up to set email alerts
|

Dominant Device Instability Mechanism in Scaled Metal–Oxide–Semiconductor Field-Effect Transistors with Hafnium Oxide Dielectric

Abstract: The negative-bias temperature instability (NBTI) and positive-bias temperature instability (PBTI) of metal-oxide-semiconductor field-effect transistors (MOSFETs) with high dielectric constant (k ) gate dielectrics have been studied by varying the physical thickness of high-k dielectric. Both PBTI and NBTI were reduced with decrease in the high-k dielectric thickness, but NBTI reduction saturated in the thin highk region. Since residual NBTI is sufficiently large to cause device instability, NBTI is still a dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…It has been reported that when the thickness of high-dielectrics is reduced to 2 nm, NBTI becomes the predominant degradation mechanism. 21) In this sense, the ultrathin SiN cap layer may play a key role in improving the overall reliability.…”
Section: Bti Mechanism Of the Hfsion Mosfetsmentioning
confidence: 99%
“…It has been reported that when the thickness of high-dielectrics is reduced to 2 nm, NBTI becomes the predominant degradation mechanism. 21) In this sense, the ultrathin SiN cap layer may play a key role in improving the overall reliability.…”
Section: Bti Mechanism Of the Hfsion Mosfetsmentioning
confidence: 99%